Amino terminus of cardiac myosin binding protein-C regulates cardiac contractility. (July 2021) - Lynch, Thomas L.; Kumar, Mohit; McNamara, James W.; Kuster, Diederik W.D.; Sivaguru, Mayandi; Singh, Rohit R.; Previs, Michael J.; Lee, Kyoung Hwan; Kuffel, Gina; Zilliox, Michael J.; Lin, Brian Leei; Ma, Weikang; et al.
Abstract: Phosphorylation of cardiac myosin binding protein-C (cMyBP-C) regulates cardiac contraction through modulation of actomyosin interactions mediated by the protein's amino terminal (N′)-region (C0-C2 domains, 358 amino acids). On the other hand, dephosphorylation of cMyBP-C during myocardial injury results in cleavage of the 271 amino acid C0-C1f region and subsequent contractile dysfunction. Yet, our current understanding of amino terminus region of cMyBP-C in the context of regulating thin and thick filament interactions is limited. A novel cardiac-specific transgenic mouse model expressing cMyBP-C, but lacking its C0-C1f region (cMyBP-C ∆C0-C1f ), displayed dilated cardiomyopathy, underscoring the importance of the N′-region in cMyBP-C. Further exploring the molecular basis for this cardiomyopathy, in vitro studies revealed increased interfilament lattice spacing and rate of tension redevelopment, as well as faster actin-filament sliding velocity within the C-zone of the transgenic sarcomere. Moreover, phosphorylation of the unablated phosphoregulatory sites was increased, likely contributing to normal sarcomere morphology and myoarchitecture. These results led us to hypothesize that restoration of the N′-region of cMyBP-C would return actomyosin interaction to its steady state. Accordingly, we administered recombinant C0-C2 (rC0-C2) to permeabilized cardiomyocytes from transgenic, cMyBP-C null, and human heart failure biopsies, and we found that normal regulation of actomyosin interaction and contractility was restored. Overall, these data provide a unique picture of selective perturbations of the cardiac sarcomere that either lead to injury or adaptation to injury in the myocardium. Graphical abstract: Unlabelled Image Highlights: Deletion of the N'-C0-C1f region of cMyBP-C results in dilated cardiomyopathy Administration of rC0-C2 to permeabilized cardiomyocytes from failing hearts restored steady-state actomyosin interactions. C0-C2 region of cMyBP-C augments contractility and thin-thick filament interactions